Classroom manual for automotive suspension & steering systems - Knowles, Don (Today's technician, 2007)
This new edition features the most current content on suspension and steering systems for today's cars, SUVs, light duty trucks and now, hybrids! The 4th Edition is teeming with new and improved content, from the latest mandatory tire pressure monitoring systems to the newest electronically-controlled suspension systems. New information on the latest front and rear suspension designs, recent developments in steering columns and air bag systems, and the latest electronic power steering gears are also discussed.